The comparative advantages of HSR, AIR, and HA on the coordinated regional economic development in China - Guo Dong Li; Wenshan Liu; You Zhi Xue; Sangbing Tsai (PLoS ONE, 2026)
This study aims to systematically compare the roles of high-speed rail (HSR), air transport (AIR), and their synergy in promoting coordinated regional economic development across different spatial scales in China. While the existing literature has primarily focused on individual transportation modes, the comparative advantages and synergistic effects of HSR and AIR on coordinated regional economic development remain understudied. To address this gap, we employ multi-dimensional panel data from 2008 to 2023, covering macro-regional, provincial, and city networks, to reveal the heterogeneous impacts and collaborative potential of these transportation networks. Our objective is to determine the optimal spatial scale for each transport mode and their collaboration to maximize coordinated regional economic development. Results demonstrate that AIR significantly enhances coordinated regional economic development at the macro-regional scale, HSR-AIR collaboration development markedly promotes coordinated regional economic development at the provincial scale, and HSR significantly strengthens coordinated regional economic development at the city scale. The dose-response model regression results further indicate that the positive effect of AIR networks on coordinated regional economic development exhibits stable enhancement with AIR development at the macro-regional scale; HSR-AIR collaboration’s promotive effect increases with its development at the provincial scale but encounters an upper growth limit; and at the city scale, HSR’s impact initially rises then declines, displaying diminishing marginal returns on coordinated regional economic development. Consequently, this study recommends formulating differentiated transport network planning policies tailored to specific spatial scales, leveraging the complementary advantages of HSR and AIR to foster coordinated regional economic development.